2013
DOI: 10.1098/rsif.2012.1040
|View full text |Cite
|
Sign up to set email alerts
|

Gold-containing bioactive glasses: a solid-state synthesis to produce alternative biomaterials for bone implantations

Abstract: A new melted bioactive system containing gold nanoparticles (AuNPs) was prepared exploiting a post-synthesis thermal treatment that allows one to modify crystal phases and nature, shape and distribution of the gold species in the glass-ceramic matrix as evidenced by UV-visible spectroscopy, transmission electron microscopy and powder X-ray diffraction analysis. In human MG-63 osteoblasts the presence of Au nþ species caused an increase of lactate dehydrogenase leakage and malonyldialdehyde production, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Similarly, around 800°C, this silicorhenanite crystalline phase was reported by several authors (Aguilar‐Reyes et al, 2017; Bretcanu et al, 2009). Aina et al (2013) specified Na 2 CaSi 2 O 6 crystalline phase at 600°C and also reported the presence of NaCaPO 4 . In this investigation, sol–gel prepared bioglass underwent thermal treatment with various parameters (different temperature and time).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, around 800°C, this silicorhenanite crystalline phase was reported by several authors (Aguilar‐Reyes et al, 2017; Bretcanu et al, 2009). Aina et al (2013) specified Na 2 CaSi 2 O 6 crystalline phase at 600°C and also reported the presence of NaCaPO 4 . In this investigation, sol–gel prepared bioglass underwent thermal treatment with various parameters (different temperature and time).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of AuNPs in bioactive glass matrix can widen the medical applicability of these materials: diagnostics, therapy, prevention and hygienic applications [ 116 , 119 , 143 ]. This depends on the promising properties of the AuNPs, such as biocompatibility, facile surface modification, stability and optical properties, which can be tuned by particle size and shape, surface chemistry and charge [ 116 , 143 ]. Concerning the toxicity of AuNPs it was found that the colloidal particles (3–100 nm) do not have any toxic effect on cell cultures, while the 1–2 nm sized AuNPs are considered dangerous due to the possibility of irreversible binding to biopolymers in the cells [ 143 ].…”
Section: Metallic Nanoparticles In Composites With Bioactive Glassmentioning
confidence: 99%
“…Many studies demonstrated that bioactive glasses with Au content do not have toxic effect [ 116 , 117 , 119 ] and their bioactivity is not affected by the presence of AuNPs [ 116 , 117 , 118 ]. One promising application of the bioactive glass with AuNP is to serve as drug delivery agents [ 116 ], as it was also shown by Jayalekshmi et al [ 119 ]. The bioactive glass–polymer composite was incorporated in the voids formed by the removal of bone tumors for controlled drug release to suppress the further tumor formation, and to enhance bone growth.…”
Section: Metallic Nanoparticles In Composites With Bioactive Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays similar glasses can be obtained by various methods such as sol-gel [9][10][11] or high energy irradiation of Au containing glass [8,12,13]. Such composites are of interest for biomedical [9,10,14] and optical [12] applications and for historical purposes as well [8,13].…”
Section: Introductionmentioning
confidence: 99%